(untitled) (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The purpose of the present work was to formulate fast dissolving tablets (FDTs) of poorly water-soluble drug Atorvastatin using natural superdisintegrants like starches extracted from Entada scandens seed powder. Objectives: The present work mainly focuses on solubility enhancement of BCS Class-II drugs using starch as superdisintegrant which improves drug release. Materials and Methods: Starches were extracted using alkali method, i.e., sodium hydroxide at 0.1%, 0.25%, and 0.5% concentrations and water from E. scandens seed powder. These starches were evaluated for various phytochemical, physicochemical tests, and acute toxicity studies. FDTs were prepared using Atorvastatin, Starch, and Croscarmellose sodium (CCS) in various concentrations using wet granulation technique. Various pre- and post-compression parameters were performed along with in vitro drug release studies, characterization studies such as Fourier transform infrared (FTIR), differential scanning calorimetry (DSC), scanning electron microscopy, X-ray diffraction (XRD), and stability studies. Results and Discussion: Phytochemical tests revealed the presence of only starch in all the extracts. Acute toxicity studies indicated the healthy condition of all mice. The starch prepared from 0.5% sodium hydroxide (E. scandens seed starch [ESS4]) showed best physicochemical properties. From in vitro dissolution studies, it was observed that formulations F5 and F11 containing 15% w/w of ESS4 and 15% w/w of CCS showed faster disintegration and enhanced dissolution rate compared with other formulations. FTIR and DSC studies revealed that there were no major interactions between the drug and excipients. XRD studies revealed the nature of formulations. Accelerated stability studies revealed that all tablets were stable. Conclusion: Thus, the tablets prepared using ESS4 revealed the superdisintegrant property of starch.